2019
DOI: 10.1002/14651858.cd012628.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene interventions for people with intellectual disabilities

Abstract: Trusted evidence. Informed decisions. Better health. Cochrane Database of Systematic Reviews Analysis 4.1. Comparison 4 Oral health (OH) training of people with intellectual disabilities (ID) versus no training, Outcome 1 Gingival inflammation short term (< weeks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 95 publications
5
77
0
1
Order By: Relevance
“…This realist review followed a published protocol and followed the RAMESES publication standards for realist reviews 10 . It was undertaken alongside a Cochrane Review, reported separately 6 . It was anticipated that the parallel use of methods would identify which interventions work (Cochrane) for whom and under what circumstances (realist), thereby generating a uniquely comprehensive understanding of what should be implemented, and how, in different settings 11,12 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This realist review followed a published protocol and followed the RAMESES publication standards for realist reviews 10 . It was undertaken alongside a Cochrane Review, reported separately 6 . It was anticipated that the parallel use of methods would identify which interventions work (Cochrane) for whom and under what circumstances (realist), thereby generating a uniquely comprehensive understanding of what should be implemented, and how, in different settings 11,12 …”
Section: Methodsmentioning
confidence: 99%
“…Thus, our starting point was the search strategy and criteria for the Cochrane Review, which included 178 randomized controlled trials and nonrandomized studies. 6 Of these, we excluded 41 published in languages other than English. We further refined by filtering for studies that provided contexts, mechanisms and outcomes that were relevant to carer‐led interventions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analyses of pooled data from comparable randomised controlled trials and some non-randomised studies (eg controlled before/after; interrupted time-series; repeated measures) are more likely than most other reviews to synthesise robust evidence on the effects of illnesses and therapies and the phenomena influencing them. 2,37,49,50 However, the credibility of the analysis towards evaluating specific interventions or establishing broad generalisations depends on the homogeneity of data from the primary trials or studies, and on the efforts of reviewers to conduct a comprehensive, transparent, unbiased, appropriately weighted and reproducible literature review. 2,8,51 Observational studies associated with side effects or rare events have also been reviewed systematically as complementary to evidence from randomised controlled trials.…”
Section: Meta-analysismentioning
confidence: 99%